2021
DOI: 10.3897/bdj.9.e71100
|View full text |Cite
|
Sign up to set email alerts
|

New insight into spatial ecology of Griffon Vulture (Gyps fulvus) on the Balkans provides opportunity for focusing conservation actions for a threatened social scavenger

Abstract: The knowledge in the behaviour and movement of endangered species is of key importance for the precise targeting and assessing the efficiency of nature conservation actions, especially considering vultures, which explore vast areas to locate ephemeral and unpredictable food resources. Therefore, a total of 51 Griffon Vultures (Gyps fulvus) from both the re-introduced population and the autochthonous Balkan Peninsula (Balkans) colonies have been tagged with GPS/GSM transmitters in recent years, in order to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
3
11
0
Order By: Relevance
“…Individual Griffon Vultures forage over huge home‐ranges (Peshev et al . 2021 and references therein), which in our study case are close to 10 000 km 2 (Arrondo et al . 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Individual Griffon Vultures forage over huge home‐ranges (Peshev et al . 2021 and references therein), which in our study case are close to 10 000 km 2 (Arrondo et al . 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Breeding parameters in the Serbian Griffon vulture population are relatively high despite the substantial increase in population size, implying that the population is far from its saturation level ( Marinkovic et al, 2021 ) further strengthening this population prospect as a reintroduction resource in the Balkan Peninsula ( Davidovic et al, 2020 , 2022 ). The latest research on the spatial ecology of Griffon vultures in the Balkans identified seven key vulture zones (one in Serbia, one shared between North Macedonia and Bulgaria, one shared between Bulgaria and Greece, two in Bulgaria, one in western Greece and one shared between Kvarner Archipelago islands in Croatia and the Julian Alps—Italy, Austria and Slovenia) ( Peshev et al, 2021 ). This research also identified that the young birds tend to migrate but always return to their nesting ground after migration due to the strong natal philopatry specific for this species and so far no or little exchange of migrant birds between these vulture zones in the Balkans was detected ( Peshev et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Again similar to badgers we would expect seasonal shifts in the form of an increase and decrease in activity depending on the time of year. [95][96][97]101 We can broadly summarise the vulture ecology we want to parametrise as follows:…”
Section: Ecology and Objectives -Vulturementioning
confidence: 99%
“…Movement speed approximated by summary statistics from previous studies, [95][96][97][98] with minimal landscape derived resistance 3. A 8-12 hour activity cycle, 100 that shifts over the year 95,96,101 Figure 11. The three resulting landscape layers to be fed into the simulation for the vulture example: shelter quality, foraging resources, movement ease.…”
Section: Ecology and Objectives -Vulturementioning
confidence: 99%